(untitled) (CIPEEX, 2025)
Play, characterized as spontaneous, enjoyable, and healthy, plays a central role in the motor development of children, especially in Elementary School I. Studies such as those by Friedmann, Rosado, and Vygotsky emphasize that playful activities are fundamental for physical, emotional, and intellectual development. Kishimoto (2017) emphasizes that play reveals children’s personalities, providing freedom to express feelings and behaviors. Motor development, according to De Paiva (2015), is a sequential process influenced by biology, tasks, and the environment. At the beginning of schooling, children refine motor skills, such as running, jumping, and balancing, which are part of their normal progress. The sociocultural context and access to play also influence this development. Freire (2007) emphasizes the need to develop motor skills considering their cognitive and social consequences. The research, based on literature reviews, indicates that play not only improves motor skills but also promotes the holistic development of the child, although inequalities in access to these activities limit the motor progress of some children.